Molecular Docking Analysis of Estrogen Receptor Î± to Phytochemistries in Asteraceae Family Compared to Tamoxifen in Breast Cancer - Umam, Dzulfiar Nasir; Pesik, Riza Novierta; Kusumawati, Ratna (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background:Tamoxifen is the first line hormonal therapy for Estrogen Receptor Î±(ERÎ±) breast cancer. Some of phytochemistries pose anticancer activities. However, data of those from Asteraceae family in Indonesia are lacking. The aim of this research is to know the binding affinities and binding locations of phytochemistries in Asteraceae family from Indonesia compared to tamoxifen on ERÎ± in breast cancer. Methods: This research wasa bioinformatic study. Subjects were3-dimensional structures ofERÎ±, tamoxifen, and phytochemistriesâs Asteraceae family obtained from Indonesian HerbalDB database, Pubchem Compound, and Protein Data Bank. Subjects were prepared by Chimera 1.10 and Open Babel. Tamoxifen was docked on ERÎ± by AutoDock Vina to know its binding affinities of ligand-receptor complex, compared to the other chosen ligands. Binding locations of ligand-reseptor were visualized by Pymol 1.7.2. Results: The docking results showed four phytochemistriesâs binding affinities whichwere stronger than tamoxifen (-9.6 kcal/mol), such as lappadilactone, friedelin, benperidol, and beta-amyrin. The visualization results showed that lappadilactone, friedelin, benperidol, beta-amyrin, taraxerol, andepifriedelanol had similar binding areas totamoxifen on ERÎ±. Lappadilactone had hydrogen bond with Tyr526 and benperidol had hydrogen bond with Trp383 on ERÎ±. Conclusions:Lappadilactone and benperidol have stronger binding affinities than tamoxifen and they have hydrogen bond with ERÎ±, but not in active sites of ERÎ±. Therefore, lappadilactone and benperidol may have ability to inhibit ERÎ± activities computationally. Keywords: Estrogen receptor Î±, molecular docking, phytocemistry, tamoxifen.